The Impact of Ekman Pumping and Transport on Dosidicus gigas (Jumbo Flying Squid) Fishing Ground by Chinese Jiggers off the Coast of Peru - Xingnan Fang; Xin Zhang; Xinjun Chen; Wei Yu (Journal of Marine Science and Engineering, 2025)
Upwelling is often associated with high productivity, biodiversity, and fishery resource abundance. This study employed a generalized additive model (GAM) to analyze the effects of Ekman pumping and transport on the abundance and distribution of jumbo flying squid (Dosidicus gigas) using wind field data and Chinese commercial fishing catch data off Peru from 2012 to 2020. The results indicate that the spatial distribution of Ekman pumping and transport exhibited significant monthly variation and exerted a considerable impact on the abundance and distribution of D. gigas. Ekman pumping fluctuated between 4.98 × 10−9 to 6.84 × 10−7 m/s, with the strongest upwelling effects observed from February to March and October to December. Ekman transport varied from 0.89 to 2.56 m3/s and peaked in August. The GAM results indicate that the catch per unit effort (CPUE) of D. gigas was significantly affected by Ekman pumping, while the latitudinal gravity centers (LATG) of D. gigas were significantly influenced by Ekman transport and chlorophyll-a concentration (Chl-a). Both hydrodynamic processes had a significant influence on Chl-a. Ekman pumping contributed greatly to upwelling formation, significantly increasing Chl-a concentration in the northern region, while strong Ekman transport pushed high-Chl-a coastal waters offshore in the central and southern regions when Ekman pumping was weaker, resulting in increasing offshore Chl-a concentrations. Furthermore, Chl-a concentration was significantly positively correlated with Ekman pumping after a two-month lag. An El Niño weakened the intensity of Ekman pumping, leading to notable declines in Chl-a concentration and D. gigas CPUE. These findings demonstrate that Ekman pumping and transport significantly influence the distribution of Chl-a, to which D. gigas is sensitive, influencing the abundance and distribution of this species off the coast of Peru.